THE BRAZILIAN JUDICIAL PROTECTION OF THE SOCIAL INCLUSION - Paula, Jônatas Luiz Moreira de (Revista de Ciências Jurídicas e Sociais da UNIPAR, 2008)
Once evidenced the Brazilian social exclusion, it is necessary to implement the public policies of social inclusion. So, the Judiciary Power presents itself as a protagonist of the rethinking of the Social Contract upon imposing the faithful execution of the budgetary law and consequently to reach the desired stability and continuity of the public politics of social inclusion.